HUBUNGAN DUKUNGAN KELUARGA DENGAN SELF CARE PADA PASIEN DIABETES MELITUS - Nur Wahyuni Munir (Borneo Nursing Journal (BNJ), 2021)
Diabetes self-care is the act of helping control blood sugar which can result in better health conditions. This study aims to see the relationship between the level of knowledge and self-care in diabetes mellitus patients at the Puskesmas Tamamaung, Makassar City. The research design used was an analytic survey with a cross sectional study approach. The sample determination was carried out by purposive sampling technique with a sample size of 41 respondents. The relationship test was performed using the Fisher Exact Test and Pearson statistical tests with a significance level of α less than 0.05. The results of this study indicate that good family support is 92.7%. The conclusion of this study is the relationship between family support and the implementation of self-care for diabetes mellitus patients at the Puskesmas Tamamaung Makassar City (ρ = 0.003). families are expected to provide support both in patient self-care and psychological.